Prediction of spatially variable unsaturated hydraulic conductivity using scaled particle‐size distribution functions. Issue 7 (26th July 2013) - Nasta, Paolo; Romano, Nunzio; Assouline, Shmuel; Vrugt, Jasper A.; Hopmans, Jan W.
<x xml:space="preserve">Abstract</x> [1] Simultaneous scaling of soil water retention and hydraulic conductivity functions provides an effective means to characterize the heterogeneity and spatial variability of soil hydraulic properties in a given study area. The statistical significance of this approach largely depends on the number of soil samples collected. Unfortunately, direct measurement of the soil hydraulic functions is tedious, expensive and time consuming. Here we present a simple and cost‐effective hybrid scaling approach that combines the use of ancillary information (e.g., particle‐size distribution and soil bulk density) with direct measurements of saturated soil water content and saturated hydraulic conductivity. Our results demonstrate that the presented approach requires far fewer laboratory measurements than conventional scaling methods to adequately capture the spatial variability of soil hydraulic properties.